Methods for synthesizing hydroxamic acids and their metal complexes - Sow, Ibrahima Sory (European Journal of Chemistry, 2024)
In previously published works, the antibacterial, antifungal, antimycobacterial and anticancer activities of hydroxamic acids (HA) and their complexes were reported. Our recently published work shows that aliphatic HA with a number of carbon atoms equal to 12 (C12) and its Fe(II), Fe(III), Ni(II), Cu(II) and Zn(II) complexes are significantly active against bacteria (Staphylococcus aureus, Escherichia coli), fungal (Candida albicans) and mycobacteria (Mycobacterium smegmatis). Furthermore, the inhibitory activities against biofilms of Mycobacterium tuberculosis, Mycobacterium bovis BCG, Mycobacterium marinum and Pseudomonas aeruginosa were observed with a large number of HA and their complexes. Suberoylanilide HA and resminostat were approved to treat cutaneous T cell lymphoma and in clinical trials to treat advanced hepatocellular carcinoma, respectively. In view of the interesting biological properties of this family of chemical compounds, the synthesis of HA has been reported in numerous research articles in recent years but this is the second review article dedicated to their synthetic methods and the first review for their complexes. The aim of this review is to highlight optimal and rational methods for the synthesis of HA and their complexes. HA are obtained in near-quantitative yields from carboxylic acid, ethyl chloroformate, N-methylmorpholine and hydroxylamine. As for their complexes, the synthesis methods described are fairly similar and would all appear to be optimal. The main criteria are the number of equivalents of HA, the type of metal salt or solvent used and the reaction conditions.